La Grèce à l’épreuve de la crise - Botopoulos, Kostas (Études helléniques / Hellenic Studies, 2014)
This article deals with the progress of the crisis in Greece since 2009, from an economic, political and institutional point of view. The first part deals more specifically with the management of the crisis; the second part analyses the characteristics and problems of the “rescue package” and especially the famous “Memorandum” signed with lenders; the third part examines the consequences of the political and social life, including the breakdown of the party system and the extension of precariousness; and the fourth part is trying to determine whether what today appears to be a turning point, both internally and on the European level, it really is.